Evaluating the implementation and impact of a volunteer navigation oncology support programme: study protocol for a pragmatic, real-world hybrid type 2 study - Charlotte Waugh; Noah Federman; Gabrielle B Rocque; D'Ambra N Dent; Emily K Hill; Ian Bostock Rosenzweig; Bonny Morris; Arif Kamal (BMJ Open)
Introduction Patient navigation is recommended by accrediting bodies such as the Commission on Cancer and is a key element in payment reform demonstration projects, due to the established benefits in reducing barriers to healthcare, improving care coordination and reducing healthcare utilisation. However, oncology practices are often resource constrained and lack the capacity to extend navigation services at the desired intensity for their patient population. The American Cancer Society (ACS) developed the ACS Community Access to Resources, Education, and Support (CARES) programme to expand navigation capacity through the training of students from local universities as volunteers to serve as non-clinical navigators to support cancer patients. Although this approach has great potential for scalability, the best approach to early implementation and impact of volunteer navigation remains unclear.Methods and analysis This pragmatic single-arm pre–post study evaluates the implementation and effectiveness of volunteer navigation for patients participating in the 2023–2024 pilot. This study will use data collected during routine care for quantitative implementation and patient outcomes. The Updated Consolidated Framework for Implementation Research will guide evaluation of early programme implementation with three initial pilot sites. This pragmatic evaluation of real-world implementation of volunteer navigation in the oncology setting will support future efforts to scale-up this intervention across US health systems.Ethics and dissemination This study was approved by University of Morehouse School of Medicine Social and Behavioral (IRB), which served as the IRB for record for this project (IRB-2025819–2). No consent required for this study protocol. ACS CARES plans to disseminate this model and include additional sites as participants in future years.